Understanding and Addressing Gender-Based Violence in Places of Worship: A Case Study in KwaZulu-Natal, South Africa - Simphiwe Promise Buthelezi; Thobani Cele; Nonkululeko Melody Zondo; Londeka Thandokuhle Mimi Nxumalo (Journal of Social and Development Sciences, 2024)
Gender-based violence (GBV) in places of worship is a prevalent issue in societies around the world, including KwaZulu-Natal (KZN), South Africa. This study investigates the occurrence, nature, and consequences of gender-based violence (GBV) in KZN's places of worship. A quantitative research approach was used to collect data, and 2835 respondents from 11 district municipalities in KZN participated. The outcomes of this study indicate a significant incidence and knowledge of GBV in places of worship. Approximately 55.38% of respondents reported being victims of GBV in places of worship. However, most of these occurrences are carefully concealed to protect the dignity of both the church and the perpetrators. Based on these findings, this study advocates a more robust legal system to protect women and children, the closing of places of worship where abuse has been documented, and the eradication of damaging gendered norms and beliefs as ways to combat GBV. This study also suggests implementing awareness and education programs, training religious leaders and community members, establishing reporting mechanisms, offering support services, advocating for policy changes, empowering marginalized groups, and investing in additional research and monitoring. These efforts are critical for fostering safer and more supportive settings in places of worship where everyone can worship without fear of violence or prejudice.